The Effectiveness Of Online Learning With Youtube Media On Islamic Religious Education Subjects At Hang Tuah 5 Middle School Sidoarjo: Efektivitas Pembelajaran Daring Dengan Media Youtube Pada Mata Pelajaran Pendidikan Agama Islam di SMP Hang Tuah 5 Sidoarjo - Walid Romas; Ainun Nadlif (Academia Open, 2021)
In 2020, the whole world has entered the era of the industrial revolution 4.0. All sectors feel the impact of this 4.0 industrial revolution, namely trade, technology, and learning that has applied digital technology in the current learning and teaching process. The changes forced by Covid-19 are so fast, that preparations for various changes are not optimal. This is also felt by the world of education, readiness to learn online (online) set by the government is almost non-existent. The subject of Islamic Religious Education in class VIII at Hang Tuah 5 Middle School in Sidoarjo uses YouTube as a medium of learning as a whole. This is because it makes it easier for educators to create material that can be accessed by all students. The purpose of this study is to determine the effectiveness of online learning and the problems of learning with youtube media on the subject of Islamic Religious Education at Hang Tuah 5 Middle School Sidoarjo. The type of research used in this research is a qualitative research with the research subject is PAI Educator, Deputy Head of Curriculum at Hang Tuah 5 Middle School Sidoarjo, using a case study approach, types and sources of qualitative and quantitative data. The data collection technique was (1) observation (2) interview (3) documentation. The data analysis technique uses descriptive qualitative data analysis techniques and the research results are described in words so as to obtain a conclusion.